Health-Related Effects at the Outbreak of COVID-19 Pandemic in Vulnerable Communities of Romania - Stănculescu, Manuela Sofia; Marin, Anca Monica (Calitatea Vieții, 2022)
This paper reports on health-related effects of the COVID-19 pandemic impact on vulnerable populations from Romania’s vulnerable communities, Roma and non-Roma. Transmission in the most marginalized communities has been expected to be particularly high as self-isolation and social distancing are difficult to pursue as a result of crammed living conditions, limited access to basic services and infrastructure. The study reports research results from a qualitative survey based on expert interviews in communities. The sample includes a total number of 34 communities, out of which 10 Roma vulnerable rural communities, 10 vulnerable rural localities and a counterfactual of 10 resilient communes. In addition, four small urban areas with large Roma neighborhoods complete the sample. Data collection has been organized in four rounds, during the period May−July, 2020. Since the lockdown, a large number of interviewees declared non-compliance with the hygiene measures for preventing COVID-19 transmission to be a problem. While in the resilient communes this problem was not reported, it appeared to be widespread in the selected vulnerable communes. The non-compliant behavior of poor and Roma people is considered an aggregated effect of a lack of access to relevant infrastructure, particularly water, and lack of finances for the necessary sanitary products. According to opinions expressed by local institutional representatives, between Round 1 and Round 3 of research (May−June 2020), a large part of the population either has never observed the hygiene rules or has relaxed after the lockdown was lifted. Constant positive evolution was reported in the resilient communes and the vulnerable non-Roma ones. This study adds knowledge on social and economic health-related effects of the COVID-19 at the level of the most vulnerable segments of Romanian society. The results underline the fact that short-term effects of the pandemic are borne unequally.